Caffeine Promotes Conversion of Palmitic Acid to Palmitoleic Acid by Inducing Expression of fat-5 in Caenorhabditis elegans and scd1 in Mice - Du, Xiaocui; Huang, Qin; Guan, Yun; Lv, Ming; He, Xiaofang; Fang, Chongye; Wang, Xuanjun; Sheng, Jun (Frontiers in Pharmacology, 2018)
The synthesis and metabolism of fatty acids in an organism is related to many biological processes and is involved in several diseases. The effects of caffeine on fatty acid synthesis and fat storage in Caenorhabditis elegans and mice were studied. After 6 h of food deprivation, adult C. elegans were treated with 0.1 mg/mL caffeine for 24 h. Quantitative reverse-transcription polymerase chain reaction showed that, among all the genes involved in fat accumulation, the mRNA expression of fat-5 in caffeine-treated C. elegans was significantly higher than that of controls, whereas fat-6 and fat-7 displayed no significant difference. Gas chromatography-mass spectrometry was used to verify the fatty acid composition of C. elegans. Results showed that the ratio of palmitoleic acid (16:1) to that of palmitic acid (16:0) was higher in the caffeine-treated group. Several mutant strains, including those involved in the insulin-like growth factor-1, dopamine, and serotonin pathways, and nuclear hormone receptors (nhrs), were used to assess their necessity to the effects of caffeine. We found that mdt-15 was essential for the effects of caffeine, which was independent of nhr-49 and nhr-80. Caffeine may increase fat-5 expression by acting on mdt-15. In high fat diet (HFD), but not in normal diet (ND) mice, caffeine induced expression of scd1 in both subcutaneous and epididymal white adipose tissue, which was consistent with the palmitoleic/palmitic ratio results by gas chromatograph analysis.In mature adipocytes, caffeine treatment induced both mRNA and protein expression of scd1 and pgc-1α. Overall, our results provided a possible mechanism on how caffeine modulates metabolism hemeostasis in vivo.